Effects of asthenospheric flow and orographic precipitation on continental rifting - Sternai, Pietro; Muller, Veleda Astarte Paiva; Jolivet, Laurent; Garzanti, Eduardo; Corti, Giacomo; Pasquero, Claudia; Sembroni, Andrea; Faccenna, Claudio (Tectonophysics, 2021)
Asthenosphere-lithosphere interactions modulated by surface processes generate outstanding topographies and sedimentary basins, but the nature of these interactions and the mechanisms through which they control the evolution of extensional tectonic settings are elusive. Basal lithospheric shearing due to plume-related mantle flow leads to extensional lithospheric rupturing and associated magmatism, rock exhumation, and topographic uplift away from the plume axis by a distance inversely correlated to the lithospheric elastic thickness. When moisturized air encounters a topographic barrier, it rises, decompresses, and saturates, leading to enhanced erosion on the windward side of the uplifted terrain. Orographic precipitation and asymmetric erosional unloading facilitate strain localization and lithospheric rupturing on the wetter and more eroded side of an extensional system. This simple analytical model is validated against thermo-mechanical numerical experiments where a rheologically stratified lithosphere above an asthenospheric plume is subject to fluvial erosion proportional to stream power during extension. Our modeling results are consistent with Paleogene mantle upwelling and flood basalts in Ethiopia synchronous to distal initiation of lithospheric stretching/rupturing in the Gulf of Aden, which progressively propagates into the Red Sea. The present-day asymmetric topography and extensional structures in the Main Ethiopian Rift may also be an effect of a Neogene-to-present orographic erosional gradient. Although inherently related to the lithosphere rheology, the evolution of continental rifts appears even more conditioned by the mantle and surface dynamics than previously thought. •Asthenospheric flow and orography condition extensional lithospheric rupturing.•Basal lithospheric shearing forces extensional rupturing off the mantle plume axis.•Orography forces extensional rupturing on the more eroded side of a rifting system.•Modeling results explain several observed features of the East African Rift System.